A potential role of autophagy-mediated vascular senescence in the pathophysiology of HFpEF - Sanhueza-Olivares, Fernanda; Troncoso, Mayarling F.; Pino-de la Fuente, Francisco; Martinez-Bilbao, Javiera; Riquelme, Jaime A.; Norambuena-Soto, Ignacio; Villa, Monica; Lavandero, Sergio; Castro, Pablo F.; Chiong, Mario (Frontiers in Endocrinology, 2022)
Heart failure with preserved ejection fraction (HFpEF) is one of the most complex and most prevalent cardiometabolic diseases in aging population. Age, obesity, diabetes, and hypertension are the main comorbidities of HFpEF. Microvascular dysfunction and vascular remodeling play a major role in its development. Among the many mechanisms involved in this process, vascular stiffening has been described as one the most prevalent during HFpEF, leading to ventricular-vascular uncoupling and mismatches in aged HFpEF patients. Aged blood vessels display an increased number of senescent endothelial cells (ECs) and vascular smooth muscle cells (VSMCs). This is consistent with the fact that EC and cardiomyocyte cell senescence has been reported during HFpEF. Autophagy plays a major role in VSMCs physiology, regulating phenotypic switch between contractile and synthetic phenotypes. It has also been described that autophagy can regulate arterial stiffening and EC and VSMC senescence. Many studies now support the notion that targeting autophagy would help with the treatment of many cardiovascular and metabolic diseases. In this review, we discuss the mechanisms involved in autophagy-mediated vascular senescence and whether this could be a driver in the development and progression of HFpEF.